Antonio Alvares de Azevedo: fractura la voz poética masculina durante la conformación de la nación en Latinoamérica (Dossier Seis miradas al cuerpo y al deseo de una poética latinoamericana desde hace cinco siglos) - Artieda Santacruz, Pedro (2017)
In the times of the formation and consolidation of Latin American nations, literary fiction constituted a stage in which many of the political processes that then took place were represented. In this frame, poets had to fulfill a determined and excluding role, implanted from the times of the Conquest, under a binary sexuality. The respected great father of the Latin American homeland, José Martí, was undoubtedly that heroic voice, brave and manly, that fit with those expected molds. Nevertheless, other authors such as the Brazilian Antonio Alvares de Azevedo, decided to fracture that hegemony and weaken the male model. In the midst of their melancholy, they staged a much more intimate and sensual poetry. Much more feminine.